2005
DOI: 10.1175/jpo2821.1
|View full text |Cite
|
Sign up to set email alerts
|

Spring Mixing: Turbulence and Internal Waves during Restratification on the New England Shelf

Abstract: Integrated observations are presented of water property evolution and turbulent microstructure during the spring restratification period of April and May 1997 on the New England continental shelf. Turbulence is shown to be related to surface mixed layer entrainment and shear from low-mode near-inertial internal waves. The largest turbulent diapycnal diffusivity and associated buoyancy fluxes were found at the bottom of an actively entraining and highly variable wind-driven surface mixed layer. Away from surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 50 publications
4
73
0
Order By: Relevance
“…4e). Richardson number Ri = N 2 /S 2 was estimated following MacKinnon and Gregg (2005). A 2 m buoyancy frequency and 16 m shear were used in the calculation.…”
Section: Water Mass Propertiesmentioning
confidence: 99%
“…4e). Richardson number Ri = N 2 /S 2 was estimated following MacKinnon and Gregg (2005). A 2 m buoyancy frequency and 16 m shear were used in the calculation.…”
Section: Water Mass Propertiesmentioning
confidence: 99%
“…More detail measurements are required before establishing a reliable parameterization. Numerous formulas which are partly empirical or based on dynamic models have been proposed to relate turbulent dissipation rate, stratification, shear, or Richardson number (Price et al 1986;Polzin 1996;MacKinnon and Gregg 2005b) by dimensional scaling. Since the measurements described in MacKinnon and Gregg (2005a) are very similar with our situation in this paper, the parameterization method given by MacKinnon and Gregg (2005a) is used to compare with our observed data.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The data indicated that the mixing was coherent at the 95 % confidence level with both shear and stratification which were coincident with the high winds. MacKinnon and Gregg (2005b) reported that the largest turbulent dissipation away from boundaries was coincident with shear from lower-mode near-inertial waves generated by passing storms. They also argued that turbulent dissipation rates increased with both shear and stratification which is also confirmed by the measurements observed in the Baltic Sea (van der Lee and Umlauf 2011); this differs from Gregg-Henyey scaling (Gregg 1989) used for the open ocean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the generation of the inertial oscillations and their dissipation was performed on the basis of turbulent dissipation rate ( ) and turbulent eddy diffusivity (k ρ ). These parameters were calculated by using the following formula (Mackinnon and Gregg, 2005;van der Lee and Umlauf, 2011;Palmer et al, 2008;Osborn, 1980):…”
Section: Methodsmentioning
confidence: 99%